Dietary Iron is Associated with Memory in Midlife: Longitudinal Cohort Study - Anna P. Rickard,; Mark D. Chatfield,; Jonathan J. Powell,; Alison M. Stephen ,; Marcus Richards, (Journal of Pharmacy and Nutrition Sciences, 2012)
This work examined associations between dietary iron and cognitive function in mid-life adults using data from the 1946 British Birth Cohort, a representative population-based sample of men and women born in England, Scotland or Wales. Linear regression was used to determine the association between dietary iron intake or a measure of available iron (calculated by adjusting iron intake for dietary modifiers that are known to inhibit or enhance iron absorption) at ages 36, 43 and 53 years and cognitive measures at ages 43 and 53 years. Cognitive measures included verbal memory, assessed by a three-trial 15-word learning task, and speed and concentration, assessed by a timed letter search task. Examining the data cross-sectionally; dietary iron at ages 43 and 53 years was positively and significantly associated with verbal memory after adjustment for potential confounders. Examining the data longitudinally; earlier dietary iron exposure was significantly associated with later verbal memory. No associations were observed between dietary iron and measures of speed and concentration when examining the data both cross-sectionally and longitudinally. The current study shows that impaired cognition, specifically memory, resulting from inadequate iron intake may extend beyond childhood and also be present in midlife. This finding, coupled with the high prevalence of people reporting iron intakes below the Lower Reference Nutrition Intake in the UK, provide reason for concern.